"We've Got Creative Differences": The Effects of Task Conflict and Participative Safety on Team Creative Performance. (18th November 2013) - Fairchild, Joshua; Hunter, Samuel T.
Abstract Although both participative safety and team task conflict are widely thought to be related to team creative performance, the nature of this relationship is still not well understood, and prior studies have frequently yielded conflicting results. This study examines the ambiguity in the extant literature and proposes that both constructs must exist in tandem. Through a study of 55 design teams, we have identified a significant interaction between task conflict and participative safety. Results suggest that both participative safety and task conflict must exist in tandem to spur team creativity, and that team creative performance must be examined at the facet level, instead of simply as a single construct. In addition, supplemental analyses suggest that teams low on participative safety and task conflict are likely able to generate more original solutions for creative tasks due to the presence of an independent, disagreeable creative member. Implications for future research and practice are further discussed.